ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI PERSEDIAAN BARANG DI TOKO MP ONE STATIONARY 16C METRO BARAT - Wahyu Nurlaila; Suyanto Suyanto; Angga Kurniawan (Jurnal Akuntansi AKTIVA, 2020)
Wahyu, Nur, Laila 2020. “Application of Inventory Accounting Information System Goods in the MP OneStationary 16C Metro Barat (Case Study of 2017 FEB UM Metro Accounting Diploma Students) ". Faculty ofEconomics and Business, University of Muhammadiyah Metro. Advisors (1) Suyanto, S.E., M.Si.Akt.CA.,ACPA., CRA. Advisors (2) Angga Kurniawan, S.E., M.Si. In business activities in this globalization era, the development of information technology isindispensable to expand business networks and to facilitate internal corporate decision-making. The level ofcompetition which is quite tight makes business actors more use of accounting information systems to managetheir business activities properly. This type of research is qualitative, namely research procedures that produce descriptive data in theform of words from the phenomena found in the field observed by the researcher. This study aims to determinethe application of accounting information systems in the MP One Stationary 16C Metro Barat. The results obtained from this study are the accounting information system implemented in the MP OneStationary Store along with the components that support the application of the Inventory Accounting Information System in the MP One Stationary Store.